Influence of towing force magnitude on the kinematics of supramaximal sprinting - Clark, D. A.; Kuhlman, S. M.; Sabick, M. B.; Pfeiffer, R. P.; Knigge, N. A.; Shea, K. G. (Boise State University, ScholarWorks, 2009)
The purpose of this study was to determine the influence of towing force magnitude on the kinematics of supramaximal sprinting. Ten high school and collegiate aged track and field athletes ran 60m maximal sprints under 5 different conditions: non-towed (NT), Tow A (2.0% body weight), Tow B (2.8%BW), Tow C (3.8%BW), and Tow D (4.7%BW). Three-dimensional kinematics of a 4-segment model of the right side of the body were collected starting at the 35m point of the trial. Significant differences were observed in stride length (SL) and horizontal velocity of the center of mass (VH) during Tow C and Tow D. For Tow D, a significant increase in the distance from the center of mass to the foot at touchdown (DH) was also observed. Contact time (CT) decreased significantly in all towing conditions, while stride rate (SR) increased slightly (< 2.0%) under towed conditions. There were no significant changes in joint or segment angles at touchdown, with the exception of a significant decrease in the flexion/extension angle at the hip during the Tow D condition. We concluded that towing force magnitude does influence the kinematics of supramaximal running. Furthermore, we suggest that coaches and practitioners adjust towing force magnitude for each individual and avoid using towing forces in excess of 3.8%BW.